Smallpox : the fight to eradicate a global scourge - Koplow, David A., 1951- (University of California Press, 2003)
Though smallpox was eradicated from the planet two decades ago, recent terrorist acts have raised the horrific possibility that rogue states, laboratories, or terrorist groups are in possession of secret stockpiles of the virus that causes the disease, and may be preparing to unleash it on target populations. Because it is a far deadlier killer than other biological warfare agents such as anthrax, and because the universal vaccination against smallpox was halted decades ago, a smallpox attack today would be nothing short of catastrophic. This clear, authoritative study looks at the long and f.